A calibration and sampling technique for quantifying the chemical structure in fires using GC/MSD analysis. (20th January 2021) - Falkenstein‐Smith, Ryan; Harris, Kimberly; Sung, Kunhyuk; Liang, Tianshui; Hamins, Anthony
SUMMARY: This work presents an approach to measure, calibrate, and verify local concentrations of combustion products in pool fires steadily burning in a quiescent environment. This study describes a method that can be used to measure and verify the chemical species present in a fire. Such information is needed to assist in the development and validation of the chemistry subroutines in computational fluid dynamic fire models. Samples are extracted along the centerline of pool fires using a thermal quenching probe. Gas species volume fractions are analyzed using a custom Agilent 5977E Series gas chromatograph fitted with a permanent gas dual‐column comprised of a Molsieve 5 Å and PoraBOND Q capillary columns in parallel flowing into mass selective and thermal conductivity detector. The system can identify and quantify a variety of stable reactant, intermediate, and product species collected from the fire, including several condensable species (eg, water, methanol, ethanol, and acetone). The time‐weighted average soot mass fraction is determined using a gravimetric sampling method. In order to solidify the legitimacy of the measured gas composition, the results are verified by implementing different techniques, including the determination of the carbon to hydrogen ratio, calculating the argon to nitrogen ratio, and comparing the total moles estimated from the chromatogram peaks to the total moles of the injected sample.